Growing Evidence for LV Unloading in VA ECMO - Soltes, Jan; Rob, Daniel; Kavalkova, Petra; Bruthans, Jan; Belohlavek, Jan (Journal of clinical medicine, 2023)
Impressively increasing availability of mechanical circulatory/cardiac support systems (MCSs) worldwide, together with the deepening of the knowledge of critical care medical practitioners, has inevitably led to the discussion about further improvements of intensive care associated to MCS. An appealing topic of the left ventricle (LV) overload related to VA ECMO support endangering myocardial recovery is being widely discussed within the scientific community. Unloading of LV leads to the reduction in LV end-diastolic pressure, reduction in pressure in the left atrium, and decrease in the LV thrombus formation risk. Consequently, better conditions for myocardial recovery, with comfortable filling pressures and a better oxygen delivery/demand ratio, are achieved. The combination of VA ECMO and Impella device, also called ECPELLA, seems to be a promising strategy that may bring the improvement of CS mortality rates. The series of presented trials and meta-analyses clearly showed the potential benefits of this strategy. However, the ongoing research has brought a series of new questions, such as whether Impella itself is the only appropriate unloading modality, or any other approach to unload LV would be beneficial in the same way. Benefits and potential risks of LV unloading and its timing are being discussed in this current review.